2022
DOI: 10.1038/s41408-021-00603-3
|View full text |Cite
|
Sign up to set email alerts
|

Effective Menin inhibitor-based combinations against AML with MLL rearrangement or NPM1 mutation (NPM1c)

Abstract: Treatment with Menin inhibitor (MI) disrupts the interaction between Menin and MLL1 or MLL1-fusion protein (FP), inhibits HOXA9/MEIS1, induces differentiation and loss of survival of AML harboring MLL1 re-arrangement (r) and FP, or expressing mutant (mt)-NPM1. Following MI treatment, although clinical responses are common, the majority of patients with AML with MLL1-r or mt-NPM1 succumb to their disease. Pre-clinical studies presented here demonstrate that genetic knockout or degradation of Menin or treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 51 publications
10
70
0
Order By: Relevance
“…S2C). Ziftomenib also increased MCL1 levels, unlikely due to MEK inhibition, as previously reported [10]. Genetic lesion(s) in TP53 were documented in approximately 9% of patients with MLL1-r AML [10].…”
Section: To the Editorsupporting
confidence: 78%
See 2 more Smart Citations
“…S2C). Ziftomenib also increased MCL1 levels, unlikely due to MEK inhibition, as previously reported [10]. Genetic lesion(s) in TP53 were documented in approximately 9% of patients with MLL1-r AML [10].…”
Section: To the Editorsupporting
confidence: 78%
“…1A, Supplementary Figs. S1C and S1D) [10]. Treatment with ziftomenib for 4 days dose-dependently induced loss of viability in OCI-AML3 and MV4-11 cells, but less so in MOLM13 and was ineffective in THP1 or NOMO-1 cells (Fig.…”
Section: To the Editormentioning
confidence: 81%
See 1 more Smart Citation
“…Fiskus and colleagues also demonstrated that the menin-KMT2A inhibitor SNDX-50469 induced differentiation and reduced the viability of the leukemic cell lines with KMT2A r or NPM mt, which was accompanied by the attenuation of BCL-2 and cyclin-dependent kinase 6 (CDK6) levels. Interestingly, the concurrent administration of SNDX-50469 with a BCL-2 inhibitor or a CDK6 inhibitor led to synergistic lethality [ 149 ]. Combination therapy with memin-KMT2A inhibitors and FLT3 inhibitors represents a promising strategy for AML with KMT2A -r or NPM1 mt and concurrent FLT3 mutation ( KMT2A r/ NPM1 mt- FLT3 mt).…”
Section: How To Deal With Specific Adverse Genetic Factorsmentioning
confidence: 99%
“…Menin inhibitors showed a potential activity in NPM1mut AML, related to MLL1 and MLL1-fusion protein inhibition. Menin inhibitors also inactivate MEIS1 transcription factor with the particularly interesting effect of downregulating its transcriptional target gene FLT3, suggesting a possible synergy with FLT3i, especially in NPM1mut-FLT3mut AML, and also in MLL-FLT3mut AML [ 115 ]. Researchers have recently demonstrated that the inhibitory effect of menin inhibitors on BCL2 protein is synergistic with that of Venetoclax in NPM1mut-FLT3mut AML [ 116 ].…”
Section: Flt3i: the Past The Present The Futurementioning
confidence: 99%